2023
DOI: 10.1111/hepr.13958
|View full text |Cite
|
Sign up to set email alerts
|

Impact of albumin–lymphocyte–platelet–C‐reactive protein index as a prognostic indicator of hepatocellular carcinoma after resection: Associated with nuclear factor erythroid 2–related factor 2

Norifumi Iseda,
Shinji Itoh,
Katsuya Toshida
et al.

Abstract: AimTo investigate the prognostic value of preoperative albumin‐lymphocyte‐platelet‐c‐reactive protein (ALPC) index in patients with hepatocellular carcinoma (HCC) undergoing curative hepatectomy. We also evaluated with the relationship of the ALPC index and phosphorylated nuclear factor erythroid 2‐related factor 2 (p‐Nrf2) levels.MethodsData were analyzed retrospectively from 256 patients who underwent resection for HCC. For cross‐validation, patients were divided into the training and testing cohort. We asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…51 Iseda's another study found that preoperative albumin lymphocyteplatelet-C-reactive protein (ALPC) index was associated with prognostic value in patients undergoing radical hepatectomy for hepatocellular carcinoma (HCC). 52 It found that a high ALPC index was an important predictor of OS and RFS in patients undergoing surgical resection for liver cancer. This may be related to the expression of phosphorylation of antioxidant factor Nrf2 in tumors.…”
Section: Neutrophil-to-lymphocyte Ratio and Platelet-to-lymphocyte Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…51 Iseda's another study found that preoperative albumin lymphocyteplatelet-C-reactive protein (ALPC) index was associated with prognostic value in patients undergoing radical hepatectomy for hepatocellular carcinoma (HCC). 52 It found that a high ALPC index was an important predictor of OS and RFS in patients undergoing surgical resection for liver cancer. This may be related to the expression of phosphorylation of antioxidant factor Nrf2 in tumors.…”
Section: Neutrophil-to-lymphocyte Ratio and Platelet-to-lymphocyte Ratiomentioning
confidence: 99%
“…This may be related to the expression of phosphorylation of antioxidant factor Nrf2 in tumors. 52 A retrospective study from Japan found that the CRP-albumin-lymphocyte index (CALLY index) is a promising biomarker for predicting postoperative outcomes in HCC patients. The study found that patients with low CALLY index (≤5) had better survival and lower recurrence rates after hepatocellular carcinoma resection.…”
Section: Neutrophil-to-lymphocyte Ratio and Platelet-to-lymphocyte Ratiomentioning
confidence: 99%